Pemanfaatan Lahan Pekarangan untuk Memenuhi Kebutuhan Pangan Keluarga di Desa Tahele Kecamatan Popayato Timur Kabupaten Pohuwato - Muhammad Kasim; Ahmad Zainuri (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
Indonesia's population growth prediction is estimated to be around 316 - 319 million (in 2025) from 255.6 million (in 2015), of course there are many problems. Lack of food can cause malnutrition. The purpose of this community service program is to use the yard to meet family food needs in preventing stunting. The location of the activity is in Tahele Village, East Popayato District, Pohuwato Regency, Gorontalo Province. The implementation period is September - October 2020. This program involves the community of Tahele Village, village apparatus and the people. They cooperate with college students in implementing the main program. The method of implementing the activity is participatory. The activities carried out are the socialization of the program plan, identification of land to be used as demonstration land, land clearing, nurseries and planting, seminars, program implementation in the community and maintenance of food crops. Of the 15 lands targeted, only 7 were successfully planted. The land is spread over 3 hamlets, namely 2 lands in Dusun Selatan, 4 lands in Dusun Tengah and 1 land in Dusun Utara. The success rate of the program is in the good category, this can be seen from the enthusiasm of the people of Tahele Village.